Arterial stiffness in chronic kidney disease: a modifiable cardiovascular risk factor?. Issue 6 (November 2019) - Pickup, Luke; Radhakrishnan, Ashwin; Townend, Jonathan N.; Ferro, Charles J.
Abstract : Purpose of review: There is an inverse, graded relationship between worsening chronic kidney disease (CKD) and increasing cardiovascular risk independent of traditional cardiovascular risk factors. Increasing arterial stiffness is a powerful predictor of cardiovascular outcomes in CKD. Developing novel therapeutic strategies to reverse this process is an attractive concept. This review presents the results of a literature survey of the last 18 months to establish if arterial stiffness can be considered a reversible cardiovascular risk factor in patients with CKD. Recent findings: Multiple potential therapeutic approaches to reduce arterial stiffness have been proposed and tested. However, arterial stiffness and blood pressure (BP) have a very close bidirectional relationship. Any change in BP will have an effect on arterial stiffness and vice versa . At present, there is no robust evidence to support the notion that arterial stiffness can be considered reversible other than as a direct consequence of reduction in BP. Summary: For now, arterial stiffness should be considered an indirectly modifiable cardiovascular risk factor through optimal control of BP. Measures of arterial stiffness should be regarded as research and risk stratification tools rather than a therapeutic target in itself.